ALGORITHMS OF ADAPTIVE LEARNING SYSTEMS (Innovative professional education, 2022)
In the transition of education to online, digital technologies are an important tool for adapting educational resources and processes. Each of the students has their own thoughts on the comfortable organization of the learning process. The basis of adaptive learning is a personalized approach to the learner. Adaptive learning systems separate what students already know from what they do not know, and use the characteristics of the students themselves to offer relevant learning material.
Keywords: vocational education; online learning; adaptive learning; educational content; digital technologies